Educational Strategy for Service Learning using STEM Activities: A Case Study of A Malaysian Secondary School - Rahim, Nurulsaidah Abdul; Mustafar, Suzaliza (ASEAN Journal of Community Engagement, 2024)
This paper discusses the Service Learning Malaysia-University for Society (SULAM) program in developing an educational strategy for science, technology, engineering, and mathematics (STEM) learning at a Malaysian secondary school. The implementation of the 60:40 policy (60% STEM and 40% non-STEM) in Malaysia is to increase the number of students studying STEM. However, as of 2022, this policy had failed to achieve this target ratio. Additionally, Malaysian students’ scores on the Program for International Student Assessment (PISA) in the categories of math, science, and language literacy decreased from 2018 to 2022. This paper argues that SULAM represents a promising approach to facilitating knowledge transfer between university students and primary and secondary school students. With the goal of examining the students’ perception and engagement in the Ingenious Content Creator program, this study recruited 50 participants from a secondary school in the Hulu Selangor District. This program was purposely conducted to nurture the interest of junior high school students in STEM and to help students find STEM and information and communication technology (ICT) more exciting and engaging. This study employed a questionnaire to examine the impact of STEM activities in the SULAM program. As a result, although 46% of students had a negative perception toward STEM, 92% of students agreed that STEM was interesting. The designated activities have successfully increased participants’ interest in STEM, generating a positive effect by facilitating learning experiences. The study demonstrates that aligning learning activities with national educational policies while also addressing such challenges can contribute to establishing a clear and meaningful connection between academic institutions and the community.